Post-traumatic Appendicitis in Pediatric Patients: A Report of Three Cases - Alvarez-Carrascal, Juan Manuel; Gualdrón-Frías, Carlos Andrés (Iatreia)
Introduction: Acute appendicitis is the most common surgical emergency in pediatric patients. However, the occurrence of this condition following abdominal trauma is rare, representing only 0.3% of all causes, with few case reports in the medical literature. Objectives: To report three clinical cases of appendicitis associated with abdominal trauma. Methods: We describe three cases of patients treated in the emergency department of Hospital Regional de Sogamoso, who presented with abdominal pain following a blunt abdominal trauma event, associated with typical clinical features of appendicitis. Results: All three patients required surgical intervention, which confirmed the diagnosis. Conclusions: Trauma is one of the less frequent etiologies for appendicitis. However, following appropriate criteria, it is possible to rule out or confirmthe diagnosis based on the patient's clinical presentation and, in some specific cases, supported by laboratory tests or diagnostic imaging.